The effect of reinvestment allowance on turnover and return on asset among manufacturing companies - Faridah, Hashim (2022)
This study explores the effect of reinvestment allowance on turnover and return on asset among manufacturing companies. Reinvestment allowance is known as one of the most prominent tax incentives. For that purpose, a quantitative approach with inland revenue data has been studied to answer the objectives of the study. Specifically, two hundred eighteen manufacturing companies that enjoy reinvestment allowance been examined, focusing on the return of qualifying asset ratio and turnover growth ratio. The findings indicate that smaller companies that invested in qualifying asset benefited more from reinvestment allowance as higher ratios of return of qualifying asset were attained. However, concerning the turnover growth, bigger companies benefited more as they experienced a higher overall growth. Suggestions for further study are having a longer time frame for research to determine the sustainability of a company and focus should be emphasised on manufacturing companies of similar interests.